What Rothbard could have done but did not do: The merits of Austrian economics without extreme apriorism - Linsbichler, Alexander (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Austrian economics emphasizes a priori components of social scientific theory. Most emphatically, Ludwig Mises and Murray Rothbard champion praxeology, a methodology often criticized as extremely aprioristic. Among the numerous justifications and interpretations of praxeology to be found in the primary and secondary literature, conventionalism avoids the charge of extreme apriorism by construing the fundamental axiom of praxeology as analytic instead of synthetic. This paper (1) explicates the tentative structure of the fundamental axiom, (2) clarifies some aspects of a conventionalist defense of praxeology, and (3) appraises conventionalist praxeology according to Rothbardian criteria. While Rothbard provides an essentialist justification of praxeology and embraces extreme apriorism, a mildly aprioristic conventionalist defense of praxeology fares better on Rothbard’s own criteria and is much more compatible with other contemporary methodological positions and economic theories.
Keywords: Austrian economics; praxeology; conventionalism; apriorism; analyticity; Ludwig Mises; Murray N. Rothbard